Effect of Prismatic Sill on the Performance of Free Flow under Sluice Gate - Jalil, Shaker A.; Sarhan, Sarhan A.; Ibrahim, Safa S. (Science Journal of University of Zakho, 2016)
Sills under sluice gates is used in hydraulic structures; their effect on the head generated upstream gates for certain rate of flow is related to the height and length of sill. A study is held in laboratory flume on four different prismatic sill heights and one model without sill by changing the gate opening four times for each model. Statistical analyses on the dimensionless physical quantities are done. A positive effect of sill on the performance of flow is noted by increasing the flow rate up to 25% for some models. The coefficient of discharge decreases with increase of relative sill height to the head upstream and increases with three other dimensionless parameters. The relative sill height to the gate opening shows the highest correlation factor with the discharge coefficient and its positive effect on the flow phenomena is 55.4%. Within the experimental measures limitations, a linear equation for predicting the discharge coefficient is proposed with Adj. R2 0.923.
Keywords: Coefficient of discharge; Flow head; Gate opening; Sill height; Sluice gate